Strategic Human Resource Management from a sustainable approach - Margel Alejandra Parra Fernández, Harold Bernardo Sukier, Reynier Israel Ramírez Molina; Giselle Paola Fernández López, Karol Martínez Cueto; Lay Raby, Nelson David (Opción, 1970)
This research describes the strategic management of human talent from a sustainable approach. Through documentary review, study and reflection of Theoretical Contributions of disciplinary, classical and current research; With an interpretation of subjectivity as the central point of the concept of human life in conjunction with society. The findings reflect new models for the management of people with Social initiatives, forgetting the environmental, thus prevailing new human resources policies; with an emphasis on human rights, diversity and the environment, involving emerging trends adapted to the glocal context.